2016
DOI: 10.1111/jace.14269
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis and Treatment of Extruded Fluoride Phosphate Glass Preforms for Optical Fiber Fabrication

Abstract: The accepted version of an article is the version that incorporates all amendments made during the peer review process, but prior to the final published version (the Version of Record, which includes; copy and stylistic edits, online and print formatting, citation and other linking, deposit in abstracting and indexing services, and the addition of bibliographic and other material.Self-archiving of the accepted version is subject to an embargo period of 12-24 months. The embargo period is 12 months for scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Work is ongoing to improve the fabrication process and eliminate these striae. In the literature, as above mentioned, only four works dealing with the fabrication and optical characterization of fluorophosphate glass fibers was reported, to the best of our knowledge [17,18,22,23]. In their work, Zou et al from Hoya Corporation reported ultra-low losses in their fibers with a minimum loss in the UV of 0.11 dB/m at 365 nm while extrinsic absorption bands were observed due to the presence of transition metal impurities at 340 nm (Fe 3þ ), 520 nm (Cr 3þ , Ni 2þ ) and 800 nm (Cu 2þ , Fe 2þ ) [17,18].…”
Section: Glass Labelmentioning
confidence: 99%
See 2 more Smart Citations
“…Work is ongoing to improve the fabrication process and eliminate these striae. In the literature, as above mentioned, only four works dealing with the fabrication and optical characterization of fluorophosphate glass fibers was reported, to the best of our knowledge [17,18,22,23]. In their work, Zou et al from Hoya Corporation reported ultra-low losses in their fibers with a minimum loss in the UV of 0.11 dB/m at 365 nm while extrinsic absorption bands were observed due to the presence of transition metal impurities at 340 nm (Fe 3þ ), 520 nm (Cr 3þ , Ni 2þ ) and 800 nm (Cu 2þ , Fe 2þ ) [17,18].…”
Section: Glass Labelmentioning
confidence: 99%
“…Although they reported on preform neck-down crystallization issues during the drawing, they achieved minimum losses of 3.05 dB/m at 405 nm after increasing the preform feed-rate and drawing speed [22]. They also showed that treatment of extruded preforms prior to fiber drawing further improved optical fiber loss to 0.5e1 dB/m [23].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the drawing process, the preform was drawn into a PCF with the desired dimensions by precisely controlling drawing parameters such as the heat temperature, drawing and perform feed speed, and nitrogen (N 2 ) content. In order to ensure the quality of the PCF, the preform surface treatment steps need to be continuously implemented [ 50 ].…”
Section: Fabrication Discussionmentioning
confidence: 99%
“…Fluoride phosphate (FP) glasses have various speciality optical fiber applications, including mid-IR lasers, UV transmission, and radiation dosimetry, of which N-FK51A soft glass is one of the most suitable types of glass for optical fibers [19]. Therefore, we select N-FK51A as the background material; its Sellmeier equation [20] can be given by:nFK51A2(λ)=1+A1λ2λ2B1+A2λ2λ2B2+A3λ2λ2B3 where A 1 = 0.971247817, A 2 = 0.219014, A 3 = 0.9046517, B 1 = 0.00472302 μm 2 , B 2 = 0.01535756 μm 2 , B 3 = 168.68133 μm 2 , and λ is free space wavelength.…”
Section: Geometry Design and Theoretical Modelingmentioning
confidence: 99%